2022
DOI: 10.1111/lit.12282
|View full text |Cite
|
Sign up to set email alerts
|

The impact of technology use on adolescents' leisure reading preferences

Abstract: There is worldwide concern about the decline in children and adolescent enjoyment of reading as documented by international and national surveys, with smartphones and other technologies often blamed for the decline. Yet, with recent rapid improvements in technologies for reading, the accelerated adoption of devices for learning during the pandemic and increased access to e-books through the public library system in Singapore, the relationship between adolescent technology use and reading may be more complex th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Laptops/computers and tablets were more likely to be shared among family members compared with smartphones, which tended to be individually owned. An earlier analysis of the survey data also showed that while print was most used for reading storybooks, non‐fiction and magazines, smartphones were the most used for reading news and comics (Loh & Sun, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Laptops/computers and tablets were more likely to be shared among family members compared with smartphones, which tended to be individually owned. An earlier analysis of the survey data also showed that while print was most used for reading storybooks, non‐fiction and magazines, smartphones were the most used for reading news and comics (Loh & Sun, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, much empirical research has investigated young people's news consumption habits with reference to technology. Evidence from economically developed nations seems to confirm that adolescents generally prefer to read digital rather than print news (Chan‐Olmsted et al, 2013; Loh & Sun, 2022; Lowenstein‐Barkai & Lev‐on, 2021; Notley et al, 2022). The smartphone is typically the preferred medium as it can be used for multiple functions, is always available, and offers ubiquitous connectivity (Boczkowski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not surprising that young adult readers are considered to be early adopters when it comes to embracing social media platforms to talk about books and reading (Gardner and Davis, 2014; Jenkins, 2009; Palfrey and Gasser, 2008; Reddan, 2022). But despite many young people having access to multiple digital platforms, most young readers still prefer to read in print formats (Faverio and Perrin, 2021; Loh and Sun, 2018). The first and second author of this paper have researched digital reading and emerging formats over the last decade, and first learned about TikTok and BookTok during the pandemic.…”
Section: Introduction and Contextmentioning
confidence: 99%